Human Umbilical Vein Endothelial Cells as a Versatile Cellular Model System in Diverse Experimental Paradigms: An Ultrastructural Perspective - Duranova, Hana; Kuzelova, Lenka; Borotova, Petra; Simora, Veronika; Fialkova, Veronika (Microscopy and microanalysis, 2024)
Human umbilical vein endothelial cells (HUVECs) are primary cells isolated from the vein of an umbilical cord, extensively used in cardiovascular studies and medical research. These cells, retaining the characteristics of endothelial cells in vivo, serve as a valuable cellular model system for understanding vascular biology, endothelial dysfunction, pathophysiology of diseases such as atherosclerosis, and responses to different drugs or treatments. Transmission electron microscopy (TEM) has been a cornerstone in revealing the detailed architecture of multiple cellular model systems including HUVECs, allowing researchers to visualize subcellular organelles, membrane structures, and cytoskeletal elements. Among them, the endoplasmic reticulum, Golgi apparatus, mitochondria, and nucleus can be meticulously examined to recognize alterations indicative of cellular responses to various stimuli. Importantly, Weibel-Palade bodies are characteristic secretory organelles found in HUVECs, which can be easily distinguished in the TEM. These distinctive structures also dynamically react to different factors through regulated exocytosis, resulting in complete or selective release of their contents. This detailed review summarizes the ultrastructural features of HUVECs and highlights the utility of TEM as a pivotal tool for analyzing HUVECs in diverse research frameworks, contributing valuable insights into the comprehension of HUVEC behavior and enriching our knowledge into the complexity of vascular biology.